Determinants Of Financial Performance In Islamic Insurance Companies Moderated By Good Corporate Governance - Selamat Muliadi; Sri Sulasmi; Santi Susanti; Aprih Santoso; Evi Maulida Yanti (JAS (Jurnal Akuntansi Syariah))
Business competition is very tight, but the development of Islamic insurance is increasingly showing a positive trend. In business entities, the company's financial performance is an important issue. This research analyzes the influence of leverage, liquidity, and company size on financial performance moderated by good corporate governance in Islamic insurance companies. This research uses a quantitative approach. The sample used in this research is the Islamic insurance industry, which regularly provides financial reports for the 2019-2021 period issued by the Indonesian Stock Exchange (IDX), totalling 15 companies. Sample collection in this research used purposive sampling. Data were analyzed using partial least squares-structural equation modelling (PLS-SEM). The results of this research show that leverage, liquidity, and company size positively affect the financial performance of Islamic insurance companies. Good corporate governance can moderate the influence of leverage, liquidity, and company size on financial performance in Islamic insurance companies. This research can be used as a reference for investors to evaluate company performance to obtain certainty in investment and for companies to increase and improve their performance.